Evaluation of patients undergoing emergency surgery in a COVID-19 pandemic hospital: a cross-sectional study - Bozkurt, Hilmi; Gür, Hüda Ümit; Akıncı, Muzaffer; Aslan, Hogir; Karakullukçu, Çiğdem; Yıldırım, Doğan (São Paulo Medical Journal, 2020)
BACKGROUND: The COVID-19 pandemic is threatening healthcare systems and hospital operations on a global scale. Treatment algorithms have changed in general surgery clinics, as in other medical disciplines providing emergency services, with greater changes seen especially in pandemic hospitals. OBJECTIVES: To evaluate the follow-up of patients undergoing emergency surgery in our hospital during the COVID-19 pandemic. DESIGN AND SETTING: Cross-sectional study conducted in a tertiary-level public hospital. METHODS: The emergency surgeries carried out between March 11 and April 2, 2020, in the general surgery clinic of a tertiary-care hospital that has also taken on the functions of a pandemic hospital, were retrospectively examined. RESULTS: A total of 25 patients were included, among whom 20 were discharged without event, one remained in the surgical intensive care unit, two are under follow-up by the surgery service and two died. Upon developing postoperative fever and shortness of breath, two patients underwent thoracic computed tomography (CT), although no characteristics indicating COVID-19 were found. The discharged patients had no COVID-19 positivity at follow-up. CONCLUSION: The data that we obtained were not surgical results from patients with COVID-19 infection. They were the results from emergency surgeries on patients who were not infected with COVID-19 but were in a hospital largely dealing with the pandemic. Analysis on the cases in this study showed that both the patients with emergency surgery and the patients with COVİD infection were successfully treated, without influencing each other, through appropriate isolation measures, although managed in the same hospital. In addition, these successful results were supported by 14-day follow-up after discharge.